Impact of potential biodegradable substrates on aromatic/ornamental plant growth and development - Sagar Ruhal; Chanchal Kumari; Susmita Shukla (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Soil mixtures play a key role in soil fertility and productivity. Keeping in view the importance of soil mixtures, our study aimed to find suitable, eco-friendly, and cost-effective soil substrates for better growth of aromatic plants.